Legal maintenance of personal safety of employees of the prosecutor’s office as an element of personnel policy - Ivanets, Mykola (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article deals with the issues of the legal providing of personal security of the employees of the public prosecutor’s office, identifying its features and the formed generalization, aimed at further theoretical development of the problems of the activities of the prosecutor’s office as a modern law enforcement agency.